ДО ПРОБЛЕМИ ФОРМУВАННЯ ТВОРЧОЇ ОСОБИСТОСТІ МАЙБУТНЬОГО ВИХОВАТЕЛЯ ДОШКІЛЬНОГО ЗАКЛАДУ (Педагогіка вищої та середньої школи, 2007)
The article deals with the definite aspects of the problem of forming a creative personality of a would be preschool teacher.